(3OjhGf Ydj GdYGedjs - (3Ydj Hf CMeO Gdabjg GdYGedjs
(3ChdgG (B:s
(3CeG HYO Efj cfJ aj YfahGf THGH, hChGf Gddgh hGdJUGHj dgLG HOJ fgGOj HKhH CQLhGfj JaJQ Yf HSe QWH LeGfj s
(3BNQgG (B:s
(3de jJb cd feQ ZjQ Pj hLd efge hbQf cej ZjQ QYOjO s
(3eDda GdOjhGf cGf MjkG SfI (B1120(3g``s
(3OjhGf Gdabjg GdYGedjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B23s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B162 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs